Differences of IL-1β Receptors Expression by Immunocompetent Cells Subsets in Rheumatoid Arthritis - Alina A. Alshevskaya; Julia A. Lopatnikova; Nadezhda S. Shkaruba; Oksana A. Chumasova; Aleksey E. Sizikov; Aleksander V. Karaulov; Vladimir A. Kozlov; Sergey V. Sennikov (Hindawi Limited, 2015)
IL-1β is involved in the induction and maintenance of chronic inflammation in rheumatoid arthritis (RA). Its activity is regulated and induced by soluble and membrane-bound receptors, respectively. The effectiveness of the cytokine depends not only on the percentage of receptor-positive cells in an immunocompetent subset but also on the density of receptor expression. The objective of this study was to investigate the expression of IL-1β membrane-bound receptors (IL-1R1 and IL-1R2) in terms of the percentage of receptor-positive cells and the number of receptors per cell in different subsets of immune cells in RA patients before and after a course of basic (excluding anticytokine) therapy and in healthy individuals. The resulting data indicate differences in the expression of IL-1β receptors among T cells, B cells, and monocytes in healthy volunteers and in rheumatoid arthritis patients. The importance of determining both the relative percentage of cells expressing receptors to immunomodulatory cytokines and the number of membrane-bound receptors per cell is highlighted by evidence of unidirectional or multidirectional changing of these parameters according to cell subset and health status.